Prospects of a new EU-MERCOSUR free trade agreement - Gratius, Susanne (2000)
Suggests that in the short term probably not much progress will be made in the negotiations between the European Union and MERCOSUR for a free trade agreement. Opines however, that the decision to begin bilateral negotiations is in itself a 'major achievement'